Exploring Psychologists Perspective on the Assessment, Management and Challenges of Twice-Exceptional Children (Journal of Asian Development Studies, 2025)
The current research explored psychologists’ perspectives on the assessment, management, and challenges related to twice-exceptional children. An exploratory research design was employed. The sample consisted of six (N = 6) psychologists selected through purposive sampling. A demographic sheet and a semi-structured interview protocol were used for participant recruitment and data collection. Braun and Clarke’s (2006) six-step method was applied for thematic analysis. Psychologists reported difficulties in assessing and managing twice-exceptional children. For assessment, they primarily relied on informal methods such as observational techniques, anecdotal records, and teacher-made checklists. Management strategies included balancing disorder and exceptionality through differentiated instruction, individualized education plans (IEPs), and strength-based approaches. The findings revealed that while psychologists were unfamiliar with the specific term “twice-exceptional children,” they understood the concept. Additionally, they encountered barriers such as the nature of the disorders, cultural differences, and parental pressure and expectations. This study highlights the need to develop comprehensive assessment tools and effective support strategies to better address the unique needs of twice-exceptional children.